Geneza kształtowania się naukowych zainteresowań św. Józefa Bilczewskiego w okresie studiów na Wydziale Teologicznym Uniwersytetu Jagiellońskiego (1880-1884) - Kałużny, Józef Cezary (Analecta Cracoviensia, 2011)
In this article I described the origins of the evolution of Józef Bilczewski’s scientific interests (1880-1884). The effect of the study, firmly established by the analysis of the source material, was the answer to the question: who and to what extent influenced the choice of interests of the young student of theology? Reflections show that at the first stage of the evolution of his scientific interests three great researchers working at the Jagiellonian University significantly influenced him: S. Pawlicki (philosopher, theologian, classic), W. Chotkowski (Church historian), W. Lepkowski (art historian, archaeologist) and perhaps also E. Skrochowski (historian of Christian art). They turned J. Bilczewski’s attention to the tradition of classic Christianity culture at the time and directed his interest towards dogmatics. Other scientists also influenced the formation of the young clergyman; at least a few priest professors can be named here: J. S. Pelczar (history of the Church and patrology, pastoral theology), Zygmunt Lenkiewicz (moral theology), Stanisław Spis and Emil Lamboy (Scripture of the Old and New Testaments). However, it can be said with confidence that it was: S. Pawlicki, W. Chotkowski and W. Lepkowski who were responsible for the dogmatic-apologetic-antique fascinations of J. Bilczewski.